Perluasan Kinerja Akustik Limbah Kayu Batang Kelapa Sawit Termodifikasi Bahan Formaldehida - Manik, Tetti Novalina; Shaliha, Shaliha; Siregar, Simon Sadok; Santoso, Tanto Budi; Yahya, Iwan; Mashuri, Mashuri; Zainuri, Muhammad; Darminto, Darminto (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2022)
Chemical modifications for waste oil palm trunks had carried out as acoustic material. This modification was conducted in two stages. Firstly, formalization with formaldehyde solution and secondly is impregnation with melamine-formaldehyde resin. Formalization was conducted in alkaline condition (pH 10) for 3 days and 5 days. Impregnation was carried out under pressure 3 bar and 5 bar and held for an hour. For completed these modification, the samples was cured at 120oC for 10 minutes and then dried at (103±2)oC to reached moisture content of less than 6%. This modification has changed the chemical structure and the morphology of wood, as shown by the FTIR and SEM results. The samples became denser, stronger and more rigid. Furthermore, the mechanical and physical properties of modified wood are also increasing. The absorption coefficient decreases with increasing formalization time and impregnation pressure. Based on trend of absorption coefficient, BKS wood can be applicated as resonant absorber with work class from A to class B and D.